NtMYB12 Positively Regulates Flavonol Biosynthesis and Enhances Tolerance to Low Pi Stress in Nicotiana tabacum - Song, Zhaopeng; Luo, Yong; Wang, Weifeng; Fan, Ningbo; Wang, Daibin; Yang, Chao; Jia, Hongfang (Frontiers in Plant Science, 2020)
Phosphorus (P) is an essential macronutrient for plant growth and development. As part of natural plant antioxidants, flavonol content is closely related to phosphorus nutritional status. However, the regulatory networks of flavonol biosynthesis under low Pi stress are still unclear. In this study, we identified an PFG-type MYB gene, NtMYB12, whose expression was significantly up-regulated under low Pi conditions. Overexpression of NtMYB12 dramatically increased the flavonol content and expression of certain flavonol biosynthetic genes (NtCHS, NtCHI, and NtFLS) in transgenic tobacco. We further demonstrated that NtMYB12 enhanced tobacco tolerance to low Pi stress by increasing the expression of Pht1 family genes（NtPT1 and NtPT2）, which led to increased Pi uptake. Altogether, our results suggest that NtMYB12 is involved in flavonol metabolism and enhances tobacco tolerance to low Pi stress, providing an advance in our understanding of the molecular mechanisms underlying plant responses to phosphorus deficiency.